Edukasi Pemanfaatan Tanaman Obat Keluarga (TOGA) untuk Meningkatkan Kesehatan Ibu dan Anak di Desa Sukaraja: Education on the Use of Family Medicinal Plants (TOGA) to Improve Maternal and Child Health in Sukaraja Village - Sinuhaji, Fatmawati; Gunarmi, Gunarmi; Ananti, Yustina (LPPM STIKES Guna Bangsa Yogyakarta, 2025)
Community service activities carried out in the form of educational activities on the use of family medicinal plants (TOGA) to improve maternal and child health in Sukaraja Village, Darul Makmur District, Nagan Raya Regency with the target being PKK cadres and mothers. The solution carried out in community service activities is in the form of providing education on the use of family medicinal plants to improve maternal and child health. The purpose of the service activity is to increase the knowledge of PKK cadres and mothers in increasing knowledge and behavior in utilizing family medicinal plants, so as to improve the degree of health of mothers and children. This educational activity was carried out in Sukaraja Village, Darul Makmur District, Nagan Raya Regency. This activity is in the form of direct education using leaflet media and herbal drink products that have been formed by the Service Team. The results showed that the knowledge of mothers in Sukaraja Village, Darul Makmur District, Nagan Raya Regency about TOGA and Temulawak innovation products increased significantly with the good category. Mothers are also very interested in practicing making Temulawak drink for the health of their mothers and children Keywords: education, family medicinal plants, improving health